The development of new methods for the assessment of oxygen radical-mediated oxidative damage to biomolecules with special reference to lipids - Patel, Ismail Yusuf (1994)
The involvement of chemically-reactive oxygen radical species (RORS) in the pathogenesis of inflammatory joint diseases has been well documented. Much of the toxicity produced by increased superoxide ion (O2.-) and hydrogen peroxide (H2O2) generation has been attributed to the production of the highly reactive hydroxyl radical (.OH) which is mediated by low-molecular-mass iron chelates such as iron-citrate complexes.